PERAN INFRASTRUKTUR DALAM PERTUMBUHAN EKONOMI PEMBANGUNAN DI WILAYAH BATU BARA - Novita, Dhea Rahma; Urrahman, Asyifa; Nasution, M.Taufiq Hidayat; Afwani S, Azra; Wulandari, Sari (Jurnal Ekonomi dan Bisnis (EK dan BI), 2024)
With an emphasis on how infrastructure affects the primary economic sectors and the well-being of local communities, this study attempts to examine how infrastructure contributes to economic growth and development in the Coal Region. In order to learn more about Batu Bara's economic growth and infrastructural development, a review of numerous papers, government reports, and related research served as the foundation for this study. Analysis of secondary data was done to find patterns and determine how infrastructure affects economic growth. This study examines Batu Bara's infrastructure development and focuses on current advancements in the energy, information technology, and transportation sectors.The analysis’s findings demonstrate how important Batu Bara’s infrastructure development is to boosting both community welfare and economic prosperity. Growing connectedness and accessibility have boosted population income, boosted investment, and expanded economic sectors. Therefore, sustained infrastructure investment in Batu Bara is thought to be essential to sustaining sustainable economic growth and guaranteeing an improvement in the population’s quality of life.